SISTEM INFORMASI PEMBAYARAN SPP MENGGUNAKAN VIRTUAL ACCOUNT BERBASIS WEBSITE PADA SEKOLAH IMAM MUSLIM BEKASI - Sabara, Edi; Heriyanto (INFOTECH journal, 2023)
Currently, the Imam Muslim School located on Jalan Raya Kranggan Gg Elang IX, Rt 002/Rw 003 Jatiraden, Jatisampurna, Bekasi, is still using manual bookkeeping and payment systems. With payment using a manual system this can make it difficult for students who want to make tuition payments, therefore the author is trying to create an Educational Contribution Payment Information System (SPP) program using a website-based virtual account using the PHP and MySQL programming languages. This system can simplify the process of operational activities in schools in managing tuition payments, reporting and also make it easier for students to make payments. Because payments can be made online through bank channels or modern payment channels such as Indomaret and Alfamart